Biochemical and molecular characteristics of citrin deficiency in Korean children - Oh, Seak Hee; Lee, Beom Hee; Kim, Gu-Hwan; Choi, Jin-Ho; Kim, Kyung Mo; Yoo, Han-Wook (Journal of human genetics, 2017)
Mutations in SLC25A13 cause citrin deficiency, which has three phenotypes: neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD), failure to thrive and dyslipidemia caused by citrin deficiency (FTTDCD) and adult-onset type 2 citrullinemia (CTLN2). The purpose of this study was to determine the mutation spectrum and the clinical and biochemical characteristics of citrin deficiency in Korean patients. Thirty-four patients were diagnosed with citrin deficiency based on mutations in SLC25A13, as verified by direct sequencing and long PCR screening of a large transposon insertion. A total of 66 alleles from 33 unrelated families of 34 patients with citrin deficiency (27 NICCD, 2 FTTDCD and 5 CTLN2) were retrospectively identified. The common pathogenic alleles were IVS16ins3kb (33%), c.851_854del (30%) and c.1177+1G>A (12%), and three novel variants were identified. Levels of citrulline, threonine, methionine, tyrosine and arginine and the threonine-to-serine ratio were higher in children with neonatal intrahepatic cholestasis caused by NICCD compared with that in patients with idiopathic neonatal hepatitis (INH). We concluded that Korean patients with citrin deficiency showed the highest frequency of the IVS16ins3kb mutation and that plasma amino-acid profiles can be used to differentiate between NICCD and INH.